2018
DOI: 10.4244/eij-d-17-00699
|View full text |Cite
|
Sign up to set email alerts
|

Randomised comparison of JUDkins vs. tiGEr catheter in coronary angiography via the right radial artery: the JUDGE study

Abstract: The Tiger-II was found superior to the Judkins 3.5L/4R regarding contrast volume use, procedural and fluoroscopy time, spasm rate and RCA imaging, and inferior regarding LAD and LCX imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 26 publications
1
34
1
Order By: Relevance
“…,000 IU in all trials. In four trials, 5,8,14,15 the primary endpoint consisted of procedure time, while in the remaining trials the primary outcomes consisted of contrast volume, 7 operator radiation exposure, 17 or strategy success. 16 The evaluation of risk of bias and overall quality of included trials are reported in Supporting Information Table S3.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…,000 IU in all trials. In four trials, 5,8,14,15 the primary endpoint consisted of procedure time, while in the remaining trials the primary outcomes consisted of contrast volume, 7 operator radiation exposure, 17 or strategy success. 16 The evaluation of risk of bias and overall quality of included trials are reported in Supporting Information Table S3.…”
Section: Resultsmentioning
confidence: 99%
“…Several randomized trials investigated the performance of either standard Judkins-shaped or dedicated catheters for transradial coronary angiography. 5,7,8,[14][15][16][17] In principle, these latter should be timesaving by avoiding repeat insertion of catheters and might concur at reducing the risk of spasm and/or occlusion through less injury of RA. 4 However, as accumulated evidence does not consistently favor one strategy over another, we performed a meta-analysis of randomized trials, which assigned ≈2,000 patients either to dual-or singlecatheter strategies for transradial coronary angiography.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From April 2017 to February 2019, 436 patients with CHD, diagnosed by coronary angiography (CAG) according to Judkins method, 27,28 were recruited from the First Naval Hospital of Southern Theater Command. They were incorporated under following conditions: (a) over 50 years old; (b) in accordance with CHD diagnostic criteria which was formulated by American College of Cardiology/American Heart Association in 2007; and (c) coronary angiography revealed that stenosis was present in one of three major vessels, or main branches of coronary was ≥50%.…”
Section: Methodsmentioning
confidence: 99%